The difference between MelP5 and melittin membrane poration - Bing Zan; Martin B. Ulmschneider; Jakob P. Ulmschneider (Scientific Reports)
Abstract Melittin, a natural peptide found in bees, has been shown to induce pore formation in cell membranes. However, its artificial mutant, MelP5 can do so at concentrations 200 times lower than melittin. The mechanism of the enhanced portion ability is not fully understood. By conducting all-atom molecular dynamics (MD) simulations, we found that MelP5 forms a stable pore that is macro-molecular sized. Our results suggest that the mutation of five amino acids from melittin reduces the electrostatic repulsion between peptides and strengthens hydrophobic interactions between MelP5 and lipid tails, resulting in the formation of a stable and larger pore. Furthermore, we found that cholesterol (CHOL), which occupies 30% in mammalian cell membranes, plays a crucial role in enhancing the pore formation of MelP5. As the amount of CHOL increases, the pore becomes larger, more stable, and forms more quickly. The presence of CHOL also promotes the formation of oligomers, which further support the pore. Our findings indicate that CHOL promotes the insertion of peptides into the membrane and reduces the amount of surface state peptides, thereby stabilizing the pore. These results highlight the important role of CHOL in membrane permeabilization by MelP5 and provide new insights into the mechanism of action of membrane-active antimicrobial peptides.